2015
DOI: 10.1063/1.4907666
|View full text |Cite
|
Sign up to set email alerts
|

Generation of kinetic Alfven waves in the high-latitude near-Earth magnetotail: A global hybrid simulation

Abstract: In this paper, effects of a fast flow in the tail plasma sheet on the generation of kinetic Alfven waves (KAWs) in the high-latitude of the near-Earth magnetotail are investigated by performing a two-dimensional (2-D) global-scale hybrid simulation, where the plasma flow is initialized by the E Â B drift near the equatorial plane due to the existence of the dawn-dusk convection electric field. It is found that firstly, the plasma sheet becomes thinned and the dipolarization of magnetic field appears around ðx;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
3
5
0
Order By: Relevance
“…The tail KAWs continue to propagate away at t = 2,527 s. By t = 2,548 s, the flux tube has moved to L121emRE (see the white field line in Figure a), and the wave energy has spread out over the field line. At later times, part of Shear Alfvén wave/KAW energy is seen to be reflected at the inner boundary, similar to that described in Guo et al (). Given that the average Alfvén speed along a tracked magnetic flux tube is around 1,500 km/s, it takes about 80–100 s for Shear Alfvén waves/KAWs to arrive at the inner boundary and be reflected.…”
Section: Simulation Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The tail KAWs continue to propagate away at t = 2,527 s. By t = 2,548 s, the flux tube has moved to L121emRE (see the white field line in Figure a), and the wave energy has spread out over the field line. At later times, part of Shear Alfvén wave/KAW energy is seen to be reflected at the inner boundary, similar to that described in Guo et al (). Given that the average Alfvén speed along a tracked magnetic flux tube is around 1,500 km/s, it takes about 80–100 s for Shear Alfvén waves/KAWs to arrive at the inner boundary and be reflected.…”
Section: Simulation Resultssupporting
confidence: 82%
“…Although KAWs have been observed in the magnetotail and ionosphere, their generation mechanisms and global transport properties are still unclear. Previous theories and simulations have shown that KAWs can be generated via various mechanisms such as magnetic reconnection (Liang et al, , ; Shay et al, ), mode conversion (Hasegawa & Chen, ; Johnson & Cheng, ), and phase mixing (Guo et al, ; Hasegawa, ; Vásconez et al, ). Shay et al () have shown the signature of KAWs generated by reconnection via a 2‐D particle‐in‐cell code.…”
Section: Introductionmentioning
confidence: 99%
“…flow by the dipole field, B x decreases and B z increases at (x, z) = (À10.5, 0.3) R E , and dipolarization appears. Such a process has been also found previously by Swift and Lin [2001] and Guo et al [2015].…”
Section: 1002/2015ja022068supporting
confidence: 86%
“…The B y patterns along the field lines connecting to the thin plasma sheet corresponding to Alfvén waves in which the perturbations in V y are correlated with those in B y . As confirmed by our previous work [ Guo et al ., ], those Alfvén waves are excited by the interaction of the ion beams with the stationary near‐Earth plasma in the low‐latitude magnetotail, and they can propagate toward higher latitudes. The V y patterns illustrate the same phenomenon, which have an in‐phase (antiphase) correlation in the Southern (Northern) Hemisphere with wave vector k ∥ B (− B ) at t =27.0 and 36.0, is based on the Walén ratio [ Landau and Lifshitz , ].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…KAWs as a natural mode of Alfven waves in hot ion plasma (Stasiewicz et al, 2000) are suggested to be generated by several different mechanisms, e.g., mode conversion (Hasegawa and Chen, 1975;Hasegawa, 1976;Lin et al, 2012;Johnson and Cheng, 1997), phase mixing (Guo et al, 2015) and magnetic reconnection (Chaston et al, 2005(Chaston et al, , 2009Liang et al, 2016;Wang et al, 2019b;Cheng et al, 2020). These waves are believed to be responsible for energy transfer from the magnetotail to 10 -1 10 0 10 1 10 2…”
Section: Discussionmentioning
confidence: 99%